2014
DOI: 10.1007/s11250-014-0689-z
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of heifer mastitis and its associated risk factors in Huanggang, Central China

Abstract: The purposes of this study were to determine the prevalence of heifer clinical mastitis (HCM) and heifer subclinical mastitis (HSCM), isolate HCM-causing bacteria, and assess the association of some risk factors in Huanggang, Central China. A total of 1,374 lactating heifers from three dairy farms were examined in the present study; 22.64% of heifers were positive for mastitis, out of which, 3.86 and 18.78% were with HCM and HSCM, respectively. Of the 67 HCM samples, 91.05% were single growth, 7.46% mixed grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
10
1
Order By: Relevance
“…The current study reported coagulase-negative Staphylococcus (CNS) as the most predominant bacteria in both clinical and subclinical mastitis. These findings agree with studies from different countries globally, which have reported CNS as emerging bacteria of mastitis [ 14 , 16 , 18 , 23 , 45 , 46 ]. However, the results contrasted with finding by Gitau et al [ 3 ], Mureithi and Njuguna, [ 28 ], and Ondiek and Kemboi [ 29 ], all in Kenya who reported Staphylococcus aureus as the dominant mastitis pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…The current study reported coagulase-negative Staphylococcus (CNS) as the most predominant bacteria in both clinical and subclinical mastitis. These findings agree with studies from different countries globally, which have reported CNS as emerging bacteria of mastitis [ 14 , 16 , 18 , 23 , 45 , 46 ]. However, the results contrasted with finding by Gitau et al [ 3 ], Mureithi and Njuguna, [ 28 ], and Ondiek and Kemboi [ 29 ], all in Kenya who reported Staphylococcus aureus as the dominant mastitis pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…chromogenes . In keeping with these findings, CNS have been implicated in the majority of subclinical udder infections in dairy cattle in various geographical regions, including Mexico [ 29 ], Finland [ 41 , 57 ], Poland [ 54 ], Uganda [ 9 ], Ethiopia [ 60 ], Rwanda [ 34 ] and China [ 19 , 59 ]. Similar CNS species profiles have been documented in intramammary infections in Canadian dairy cattle [ 15 ].…”
Section: Discussionmentioning
confidence: 75%
“…The prevalence of antibiotic resistant bacteria may be an indicator of levels of antimicrobial use in livestock. Some studies have been carried out in Zambia 4 and elsewhere 5 6 but these were primarily in relation to specific diseases such as mastitis or diarrhoea. There is, however, little information on the prevalence of antimicrobial resistance from the commensal flora of the wider healthy population and how this may be associated with antibiotic use and other farm management practices.…”
mentioning
confidence: 99%